Multiple Traffic Light Food Labeling Acceptance Among Students: Systematic Literature Review - Jain, Riya (Journal of Educational Research and Policies, 2026)
Prevalence of overweight and obesity are escalating not only among adults but also children and adolescents. Evidence suggest that effective food label helps consumers to make quick and easy decision on healthy and less healthy products based on the key nutrients such as sodium, fat, saturated fat, and sugar content. No reviews have been published on multiple traffic light (MTL) food label as a tool used to prevent obesity among students. A search of three databases (September 2024 to October 2024) and gray - literature sources in English (2012 – 2024) were retrieved. A final of 19 studies met the inclusion criteria. The analysis showed a more salient type of food label is called the MTL demonstrated to be superior in perceived healthfulness of food products and purchased intention compared to other food label used among students. Therefore, educational institutional as a primary setting for promoting healthy eating behaviors is well recognized in reducing obesity risks due to time spent in first 2 decades of their life.